Thermal analysis and prediction of phase equilibria in ternary Pb-Zn-Ag system - Živković D.; Minić D.; Manasijević D.; Šestak J.; Živković Ž. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Ternary Pb-Zn-Ag system is typical for some physicochemical processes going on in refining phase in the extractive metallurgy of lead. Therefore, investigation of mentioned system is important from both theoretical and practical research of the phenomena occurring during the lead desilverizing process. The results of experimental investigation using differential thermal analysis (DTA) and thermodynamic calculation of phase equilibria in Pb-Zn-Ag system according to CALPHAD method, in the sections with Zn:Ag mass ratio equal to 90:10, 70:30 and 50:50, are presented in this paper.